EKONOMI POLITIK INISIATIF ONE BELT ONE ROAD TIONGKOK [ONE BELT ONE ROAD AS CHINA'S POLITICAL ECONOMIC INITIATIVE] - Mercy Widjaja (Universitas Pelita Harapan, 2019)
This study analyzes the political motives behind China’s economic policy, known as One Belt One Road (OBOR) Initiative. OBOR offers help to developing country, including Indonesia, to develop their infrastructure and domestic industries. This initiative can enlarge China's political power on the global scene, and pose a greater threat to the United States. To collect data and arguments about China's political and economic position, this study uses an explanative-qualitative method. Neorealism, hegemony stability, regionalism, and political economy are theories that are used to shape the thinking frameworks and to solve the existing problems. China also aims for greater power in the region, to secure the country’s interest. According to neorealism theory, a country's behavior is a manifestation of the country's interests and the only way to secure the country is by becoming a strong state. The stronger the state, the less chance that the country can be attacked. That means, China’s OBOR could also create conflict of interests with other countries.